Hydrolipidic Characteristics and Clinical Efficacy of a Dermocosmetic Formulation for the Improvement of Homeostasis on Oily Mature Skin - Letícia Kakuda; Maísa Oliveira de Melo; Patrícia Maria Berardo Gonçalves Maia Campos (Life, 2022)
Background: Although the scientific literature associates mature skin with dry skin and the secretion of sebum on the face decreases over the years, in tropical countries, such as Brazil, mature skin can still present oily characteristics. Thus, the knowledge of the hydrophilic characteristics of mature skin is fundamental to help the development of more effective treatments for this skin type. In this context, the study aimed to evaluate the hydrophilic characteristics and the clinical efficacy of a cosmetic formulation for mature skin added with alfalfa and lentil extracts by using biophysical and skin imaging techniques. Methods: Twenty-eight healthy females aged between 45 and 59 years were enrolled. Measurements of the stratum corneum water content, sebum content, transepidermal water loss, skin microrelief, and pores count were performed before and after the 28-day formulation application. Results: The mature skin presented as oily with wrinkles and pores. The proposed formulation significantly reduced the sebum content and the number of fine and large pores and improved skin microrelief and hydration after a 28-day period of the application when compared to the vehicle. Conclusions: The proposed formulation was effective in oily mature skin treatment, improving its general skin aging and oiliness conditions, and reducing pores count in just 28 days.